(untitled) (Research, Society and Development, 2022)
Chronic Kidney Disease (CKD) is a progressive and irreversible deterioration of renal function and its clinical evolution is insidious and, therefore, identifying people susceptible to developing it, or in its initial stages as early as possible, is essential for a preventive approach and mitigation of the evolution. for the terminal phase. The objective of this study was to analyze the assistance to patients with CKD in primary health care. The methodology used was a systematic review that followed the PRISMA protocol to design and carry out the study. Eligibility criteria were observational, experimental studies and gray literature that address the care of patients with CKD in primary care. Exclusion criteria were expert opinion studies, letters to the editor and review articles. The information sources were: Pubmed, web of Science, Sciencedirect and BVS databases. The selection of articles was carried out independently with the aid of Rayyan software. The descriptors used were Renal Insufficiency, Chronic; Health Services Accessibility and Primary Health Care registered with MeSH and DeCs. The search result was 999 studies and after the exclusion and eligibility criteria, the final sample consisted of 11 articles. All the works listed for this study identified a weakened assistance to the chronic renal patient in primary health care. It is concluded that people with chronic kidney disease in the non-dialysis phase do not receive adequate assistance in primary care services to preserve kidney health.